Surface modification of carbon dots with tetraalkylammonium moieties for fine tuning their antibacterial activity - Sviridova E. V. Elizaveta Vitaljevna; Barras A. Alexandre; Addad A. Ahmed; Plotnikov E. V. Evgeny Vladimirovich; Di Martino A. Antonio; Dominique D. Deresmes; Nikiforova K. A. Ksenia Alekseevna; Trusova M. E. Marina Evgenievna; Guselnikova O. A. Olga Andreevna; Szunerits S. Sabine; Postnikov P. S. Pavel Sergeevich; Boukherroub R. Rabah (2022, 2022)
Title screen